A welding method for tantalum and titanium
Through ultrasonic welding technology through frictional heat generation and plastic deformation at low temperatures, the metallurgical combination of tantalum and titanium is achieved, solving the problem that traditional welding is difficult to connect high-melting metals, and improving welding quality and energy efficiency.
Patent Information
- Application Number
- CN202411162526.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-08-23
AI Technical Summary
Traditional welding technology is difficult to effectively connect high-melting metals tantalum and titanium at low temperatures, and it is easy to produce oxidation and heat-affected zones, affecting welding quality.
Ultrasonic welding method is adopted to frictionally generate heat and plastic deformation of the overlapping interface between tantalum and titanium at low temperatures through pre-pressure and ultrasonic vibration, so as to achieve atomic diffusion and connection, and form metallurgical bonding.
Effective welding of tantalum and titanium is achieved at relatively low temperatures, reducing energy consumption, and improving the strength and heat resistance of the welded joints, avoiding the high-temperature melting and oxidation problems in traditional welding.
Smart Images

Figure CN118682265B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of welding, and in particular to a welding method for tantalum and titanium. Background Art
[0002] In some special fields, such as military, aerospace, nuclear and chemical fields, traditional metals can no longer meet the requirements of high temperature resistance, high strength, corrosion resistance, etc., so it is inevitable to use some special metals, such as tantalum and titanium. Tantalum is a high melting point metal with a melting point of up to 2996℃ and a very small thermal expansion coefficient. Tantalum has extremely high corrosion resistance and does not react with hydrochloric acid, concentrated nitric acid and aqua regia under both cold and hot conditions. However, the disadvantages of tantalum's high price and high cost greatly limit its application. Titanium is a transition metal with a melting point of 1668℃ and has two structures: α-Ti and β-Ti. The main characteristics of titanium are low density, high mechanical strength, good heat resistance, corrosion resistance, etc. Moreover, the cost of titanium is much lower than that of tantalum, so welding tantalum and titanium can greatly reduce costs while meeting the use requirements.
[0003] Traditionally, it is generally believed that refractory metals must be melted before obtaining a good welded joint. For example, in the prior art, JOACHIM HOSSICK-SCHOTT et al. published a paper titled Latent Cracking of Tantalum-Titanium Welds Due to Hydrogen Embrittlement in The Minerals, Metals & Materials Society. He used resistance welding to weld tantalum wire to titanium plate, but brittle cracks were observed near the weld, which would affect the quality of the welded joint. In addition, for metal materials with ultra-high melting points, it is challenging to generate such a high working temperature during welding, especially considering that titanium has a great affinity with oxygen and other gaseous elements at ultra-high temperatures, and is prone to produce metallic compounds. At the same time, combined with the tantalum-titanium binary phase diagram (such as Figure 1 ), the maximum solubility of Ta in α-Ti at 600°C is only 2% (wt), and whether refractory metals can achieve effective connection below this temperature needs further exploration. Therefore, how to reduce the welding operation temperature, thereby reducing the difficulty of operation and the potential oxidation and heat-affected zone (HAZ), and then forming a good tantalum-titanium welded joint at low temperature is the focus and challenge of tantalum and titanium welding. Summary of the invention
[0004] The purpose of the present invention is to solve at least one of the technical problems existing in the prior art and to provide a welding method for tantalum and titanium.
[0005] The technical solution of the present invention is as follows:
[0006] The present invention provides a method for welding tantalum and titanium, comprising the following steps:
[0007] The titanium is placed on the base of the ultrasonic welding equipment;
[0008] Lapping tantalum on a side of the titanium facing away from the base;
[0009] Controlling the ultrasonic electrode tip of the ultrasonic welding device to move toward the base until it contacts the tantalum, and pre-pressing the tantalum and the titanium with preset pre-pressing parameters, wherein the preset pre-pressing parameters include: a pre-pressing pressure of 1.4-1.6 kN, and a pre-pressing time of 0.8-1.2 s;
[0010] The ultrasonic electrode tip is controlled to weld the tantalum and the titanium with preset welding parameters, wherein the preset welding parameters include: ultrasonic amplitude of 56-64 μm, welding pressure of 1.4-1.6 kN, welding energy of 1900-2100 j, welding frequency of 20-22 kHz, and welding time of 0.8-1.2 s.
[0011] Optionally, the pre-pressing pressure is 1.45-1.55 kN, and the pre-pressing time is 0.9-1.1 s;
[0012] The ultrasonic amplitude is 58-62 μm, the welding pressure is 1.45-1.55 kN, the welding energy is 1950-2050 j, the welding frequency is 20-21 kHz, and the welding time is 0.9-1.1 s.
[0013] Optionally, the pre-pressing pressure is 1.5 kN, and the pre-pressing time is 1 s;
[0014] The ultrasonic amplitude is 60 μm, the welding pressure is 1.5 kN, the welding energy is 2000 j, the welding frequency is 20 kHz, and the welding time is 1 s.
[0015] Optionally, the welding method further comprises:
[0016] The ultrasonic electrode tip is controlled to move toward the base until at least a portion of each welding tooth on the ultrasonic electrode tip and at least a portion of each welding tooth on the base are respectively embedded in the tantalum and the titanium, and welding grooves corresponding to the welding teeth are formed on the tantalum and the titanium, respectively.
[0017] Optionally, the welding method further comprises:
[0018] The ultrasonic electrode tip is controlled to move toward the base until at least a portion of each welding tooth on the ultrasonic electrode tip is embedded in the tantalum and the tantalum is plastically deformed to be embedded in the titanium.
[0019] Optionally, the welding groove is pyramidal in shape, the depth of the welding groove is 0.13-0.23 mm, the width of the top opening of the welding groove is 0.5-1.0 mm, and the side wall of the welding groove is at an angle of 40-50° to the ultrasonic vibration direction.
[0020] Optionally, the depth of the welding groove on the tantalum is 0.18-0.22 mm, and the depth of the welding groove on the titanium is 0.13-0.17 mm.
[0021] Optionally, the width of the top opening of the welding groove is 0.6-0.9 mm, and the side wall of the welding groove is at an angle of 45° to the ultrasonic vibration direction.
[0022] Optionally, a plurality of rows of welding grooves corresponding to the welding teeth are formed on the tantalum and the titanium, respectively, and the top openings of adjacent rows of welding grooves are connected, and the distance between the bottoms is 0.5-1.0 mm.
[0023] Optionally, the thickness of the tantalum is 0.08-0.12 mm, the thickness of the titanium is 1.5-1.7 mm, and the overlapping distance between the two is 14-16 mm.
[0024] Optionally, before the step of placing titanium on a base of an ultrasonic welding device, the welding method further comprises:
[0025] Place tantalum and titanium in an ultrasonic cleaner and clean for 10-15 minutes. The cleaning agent is water and alcohol in a volume ratio of 3-5:1.
[0026] The cleaned tantalum and titanium are dried in a vacuum drying furnace at a drying temperature of 60-80°C for 1-2 hours.
[0027] The present invention has at least one of the following beneficial effects:
[0028] The present invention provides a new method for connecting dissimilar materials without relying on melting and atmospheric protection. The metals tantalum and titanium with ultra-high melting points are effectively connected at a relatively low temperature by ultrasonic welding with specific welding parameters. The present invention first pre-presses by welding pressure in the manner of tantalum on top and titanium on the bottom. Then, under the combined action of welding pressure and ultrasonic vibration, friction heat generation and plastic deformation occur between the overlapping interfaces of tantalum foil and titanium plate, so that the atoms of tantalum and titanium diffuse and connect, thereby completing the welding of tantalum and titanium. The welding method of the present invention can partially transform the original hexagonal titanium (α-Ti) into cubic titanium (β-Ti, BCC structure), and realize the metallurgical bonding of tantalum and titanium at the welding interface.
[0029] High-speed infrared temperature monitoring shows that the temperature of the weld joint during welding operation under this specific parameter is only about 600°C, which is only 32.61% and 18.15% of the melting points of pure titanium and pure tantalum. Compared with other high-energy input melting welding in the prior art, the method of the present invention saves energy. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is the tantalum-titanium binary phase diagram;
[0031] Figure 2 : The ultrasonic welding system used in the embodiment, wherein: (a) a real picture of an ultrasonic welder, (b) a schematic diagram of tantalum-titanium welding, and (c) a schematic diagram of ultrasonic welding;
[0032] Figure 3 The morphology and indentation measurement diagrams of the welding joint in the embodiment, wherein: (a) the morphology diagram of the upper surface of the joint, (b) the 3D view of the joint, (c) the indentation measurement diagram of the joint, and (d) the morphology diagram of the lower surface of the joint;
[0033] Figure 4 The cross-sectional morphology diagrams of the welded joints in the embodiments, wherein: (a) cross-sectional morphology diagram, (b) welded interface diagram, (c) welded interface magnified diagram, (d) welded interface scanning electron microscope diagram, (e) titanium distribution diagram in the welded joint, (f) tantalum distribution diagram in the welded joint;
[0034] Figure 5 Schematic diagram of the TEM lamella preparation process in the embodiment, including (a) target position, (b) platinum deposition, (c) FIB cutting, (d) TEM lamella, (e) EDS mapping of the target, and (f) EDS line drawing result of the joint interface;
[0035] Figure 6 TEM results of the welding interface in the embodiment, wherein: (a) bright field image of the thin slice, (b) SEAD image of the tantalum region, (c) theoretical pattern of tantalum on the crystal zone axis
[100] , (d) enlarged image of the thin slice, (e) SEAD image of hexagonal titanium (α-Ti), (f) theoretical pattern of hexagonal titanium on the crystal zone axis
[001] , (g) EDS scanning result image of the thin slice, (h) SEAD image of cubic titanium (β-Ti), (i) theoretical pattern of cubic titanium on the crystal zone axis
[110] ;
[0036] Figure 7 HRTEM images of the bonding interface between tantalum and titanium in the examples, wherein (a) hexagonal titanium, (b) cubic titanium, (c) tantalum, (d) refined grains of tantalum, (e) phase boundary between α-Ti and β-Ti, and (f) bonding interface between tantalum and titanium;
[0037] Figure 8Figures of tensile tests of welded joints in the embodiments, including (a) macroscopic morphology of tensile test, (b) schematic diagram of tensile process, (c) tensile curve of joint, (d) sample after stretching, (e) cross-sectional morphology of bearing surface, (f) tensile curve of base material, and (g) tensile samples of pure tantalum and titanium;
[0038] Fig. 9 are hardness test diagrams of the welded joints in the embodiments, wherein (a) a schematic diagram of the indentation position, (b) the results of the 1st and 2nd rows, (c) the results of the 1st and 2nd columns, (d) the hardness of pure tantalum, and (e) the hardness of pure titanium;
[0039] Fig.10 is the temperature inside the nugget in the embodiment, wherein (a) the thermal image of the nugget, (b) the peak temperature of the nugget surface, and (c) the temperature variation along the electrode indentation;
[0040] Fig.11 Plastic winding and connection mechanism of titanium and tantalum, including: (a) SEM image of the bottom of the pyramid indentation, (b) BSE imaging of the welding interface, (c) distribution of Ti element, (d) distribution of Ta element, (e) EDS spectrum results of the welding interface, (f) EDS results of point 1, (g) EDS results of point 2, (h) enlarged image of the welding interface, (i) BSE imaging of the enlarged interface, and (j) EDS line scan results of the tantalum-titanium welding interface. DETAILED DESCRIPTION
[0041] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0042] An embodiment of the present invention provides a method for welding tantalum and titanium, which is performed by using an ultrasonic welding device. The ultrasonic welding device includes a base and an ultrasonic electrode tip located directly above the base. Driven by other components, the ultrasonic electrode tip can apply a vertical downward welding pressure to the workpiece to be welded on the base, and can also apply horizontal ultrasonic vibration to the workpiece to be welded along with the welding head. The welding method includes the following steps:
[0043] The titanium is placed on the base of the ultrasonic welding equipment;
[0044] Lapping tantalum on a side of the titanium facing away from the base;
[0045] Controlling the ultrasonic electrode tip of the ultrasonic welding device to move toward the base until the ultrasonic electrode tip contacts the tantalum, and pre-pressing the tantalum and the titanium with a vertical downward pre-pressing pressure of 1.4-1.6 kN and a pre-pressing time of 0.8-1.2 s;
[0046] The ultrasonic electrode tip is controlled to weld the tantalum and the titanium with preset parameters, that is, the ultrasonic welding equipment is controlled to simultaneously apply a vertical downward welding pressure and ultrasonic vibration in a horizontal direction to the tantalum and the titanium with preset parameters, wherein the preset parameters include: an ultrasonic amplitude of 56 to 64 μm, a welding pressure of 1.4 to 1.6 kN, a welding energy of 1900 to 2100 j, a welding frequency of 20 to 22 kHz, and a welding time of 0.8 to 1.2 s.
[0047] In this embodiment, pre-pressing is first performed using pre-pressing pressure, and then ultrasonic vibration is started. Under the combined effect of welding pressure and ultrasonic vibration, frictional heat and plastic deformation occur between the overlapping interfaces of tantalum and titanium, and they are connected together. By using this welding method, tantalum and titanium, metals with ultra-high melting points, can be effectively connected at a relatively low temperature.
[0048] In some embodiments, the pre-pressing pressure is 1.45~1.55 kN, the pre-pressing time is 0.9~1.1 s, the ultrasonic amplitude is 58~62 μm, the welding pressure is 1.45~1.55 kN, the welding energy is 1950~2050 j, the welding frequency is 20~21 kHz, and the welding time is 0.9~1.1 s.
[0049] In some embodiments, the pre-pressing pressure is 1.5 kN, the pre-pressing time is 1 s, the ultrasonic amplitude is 60 μm, the welding pressure is 1.5 kN, the welding energy is 2000 j, the welding frequency is 20 kHz, and the welding time is 1 s.
[0050] In some embodiments, Figure 2 As shown, the bottom surface of the ultrasonic electrode tip and the top surface of the base of the ultrasonic welding equipment are provided with at least one row of welding teeth protruding outward. Under the action of welding pressure, the welding teeth can be embedded in the tantalum foil and the titanium plate to generate heat by friction, so that the tantalum foil and the titanium plate are welded together. The welding teeth have two main functions: one is to increase the contact area with the tantalum foil and the titanium plate to be welded. The welding teeth can increase the contact area between the weld point and the substrate, and the increased contact area helps to better transmit the ultrasonic vibration energy, making the welding more firm, thereby improving the welding strength. The second is to prevent slipping. The design of the welding teeth helps to prevent the workpiece and the welding surface from slipping during the ultrasonic vibration process; by increasing the friction, the welding teeth can ensure that the vibration energy is effectively transmitted to the workpiece, thereby achieving high-quality welding.
[0051] Therefore, the welding method also includes: controlling the tip of the ultrasonic electrode to move toward the base until at least a portion of each welding tooth on the tip of the ultrasonic electrode and at least a portion of each welding tooth on the base are respectively embedded in the tantalum and the titanium, and welding grooves corresponding to the welding teeth are formed on the tantalum and the titanium, respectively.
[0052] In some embodiments, Figure 2 As shown in (b), the thickness of tantalum is smaller than the height of the welding tooth, so the welding tooth can cause the tantalum to undergo plastic deformation and embed into the titanium.
[0053] Therefore, the welding method also includes:
[0054] The ultrasonic electrode tip is controlled to move toward the base until at least a portion of each welding tooth on the ultrasonic electrode tip is embedded in the tantalum and the tantalum is plastically deformed to be embedded in the titanium.
[0055] In some embodiments, the welding teeth are in the shape of a pyramid, the height of the welding teeth is 0.24-0.26 mm, the bottom width is 0.9-1.1 mm, and the side of the welding teeth is at an angle of 40-50° to the ultrasonic vibration direction. Specifically, the welding teeth can be a triangular pyramid, a quadrangular pyramid, a pentagonal pyramid, or a hexagonal pyramid, the height of the welding teeth, that is, the vertical distance from the vertex of the pyramid to the bottom surface, is 0.24-0.26 mm, the bottom width of the welding teeth, that is, the bottom edge width of the side of the pyramid, is 0.9-1.1 mm, and the side of the welding teeth is at an angle of 40-50° to the ultrasonic vibration direction, that is, any side of the pyramid is at a horizontal direction.
[0056] Therefore, the welding teeth will form welding grooves of the same shape on tantalum and titanium, so the welding groove is approximately pyramidal, the height of the welding groove is 0.13~0.23mm, the width of the top opening of the welding groove is 0.5~1.0mm, and the side wall of the welding groove is at an angle of 40~50° to the direction of ultrasonic vibration.
[0057] In some embodiments, the height of the welding tooth is 0.25 mm, the bottom width is 1 mm, and the side surface of the welding tooth is at an angle of 45° to the ultrasonic vibration direction.
[0058] The width of the top opening of the welding groove is 0.6-0.9 mm, and the side wall of the welding groove is at an angle of about 45° to the direction of ultrasonic vibration.
[0059] The depth of the welding groove on the tantalum is 0.18~0.22mm, and the depth of the welding groove on the titanium is 0.13~0.17mm, that is, the cone indentation depth of the upper surface of the weld joint formed after welding tantalum and titanium is 180~220μm, and the cone indentation depth of the lower surface is 130~170μm.
[0060] In some embodiments, the number of welding teeth is several rows, each row has several welding teeth, the bottoms of adjacent rows of welding teeth are closely connected, and the distance between the vertices is 0.9-1.1 mm. The number of rows of welding teeth can be determined according to actual needs, such as 3-20 rows; the number of welding teeth in each row can also be determined according to actual needs, such as according to the width of tantalum and titanium, for example, 5-20 per row. Using multiple rows of welding teeth and the bottoms of adjacent welding teeth are closely connected and the vertices are separated by a certain distance can greatly increase the density of welding teeth, thereby increasing the contact area and friction with the tantalum and titanium to be welded, and improving the welding strength.
[0061] Therefore, several rows of welding grooves corresponding to the welding teeth are formed on the tantalum and the titanium, respectively, and the top openings of the welding grooves in adjacent rows are connected, and the distance between the bottoms is 0.5-1.0 mm.
[0062] In some embodiments, the thickness of the tantalum to be welded is 0.08-0.12 mm, the thickness of the titanium to be welded is 1.5-1.7 mm, and the overlap distance between the two is 14-16 mm.
[0063] Since tantalum is relatively thin and the height of the welding teeth is greater than the thickness of tantalum, during welding, the welding teeth on the tip of the ultrasonic electrode can be embedded in the tantalum and cause the tantalum to undergo plastic deformation and be embedded in the titanium, thereby facilitating the welding of tantalum and titanium.
[0064] In some embodiments, the tantalum is a tantalum foil, and the titanium is a titanium plate. The length and width of the tantalum foil and the titanium plate are 20 mm×15 mm.
[0065] In some embodiments, the method further includes the steps of cleaning and drying the tantalum and titanium to be welded before welding, the steps comprising:
[0066] Place the tantalum and titanium to be welded in an ultrasonic cleaner for 10 to 15 minutes, using a volume ratio of 3 to 5:1 of water and alcohol as the cleaning agent;
[0067] The cleaned tantalum and titanium are dried in a vacuum drying furnace at a drying temperature of 60-80°C for 1-2 hours.
[0068] Cleaning tantalum and titanium before welding can remove oil stains and prevent them from affecting the welding effect.
[0069] From the surface morphology of the weld joint, it can be seen that both the upper surface and the lower surface of the weld joint have indentations of a certain depth, indicating that the method of the present invention achieves effective connection between tantalum and titanium.
[0070] In some embodiments, the ultrasonic welding device is a SONICS MSC 2500-20 ultrasonic welding system, such as Figure 2 shown.
[0071] The use of this equipment for welding can achieve better welding effects of tantalum and titanium.
[0072] The present invention is further described in detail below with specific examples, but the present invention is not limited to the following specific examples.
[0073] Example
[0074] This embodiment provides a method for welding tantalum foil and titanium plate. The detailed schematic diagram of the welding process is as follows: Figure 2 As shown, the ultrasonic welding equipment used in this embodiment is a SONICS MSC 2500-20 ultrasonic welding system, which specifically includes the following steps:
[0075] (1) The materials used in the present invention are pure tantalum and industrial pure titanium (TA2), wherein the thickness of the titanium plate is 1.6 mm and the thickness of the tantalum foil is 0.1 mm. With the help of a linear cutting machine, the tantalum foil and the titanium plate are processed into thin sheets with a length and width of 20 mm×15 mm.
[0076] (2) Place the tantalum foil and titanium plate in an ultrasonic cleaner and clean them for 15 minutes. The cleaning agent is water and alcohol in a volume ratio of 4:1. Then, use a vacuum drying furnace to dry the cleaned tantalum foil and titanium plate at a drying temperature of 60°C and a drying time of 2 hours.
[0077] (3) A SONICS MSC 2500-20 ultrasonic welding system is used for solid-state connection. The maximum power of the equipment is 2.5 kW. Figure 2 As shown, the SONICS MSC 2500-20 ultrasonic welding system includes a base and an ultrasonic electrode tip located directly above the base. The ultrasonic electrode tip is connected to the welding head, and the welding head is connected to components such as transducers and sensors. Driven by other components, the ultrasonic electrode tip can apply a vertical downward welding pressure to the workpiece to be welded on the base along with the welding head, and can also apply horizontal ultrasonic vibration to the workpiece to be welded along with the welding head. The bottom surface of the ultrasonic electrode tip and the top surface of the base both have welding teeth protruding outward. Under the combined action of welding pressure and ultrasonic vibration, the welding teeth can be embedded in the tantalum foil and the titanium plate to generate heat by friction, which helps to weld the tantalum foil and the titanium plate together. The welding teeth in this embodiment are pyramid-shaped, with a height of 0.25 mm and a bottom width of 1 mm. The side of the welding teeth is at an angle of 45° to the ultrasonic vibration direction (horizontal direction). The ultrasonic electrode tip has 32 welding teeth, neatly arranged in four rows, each row perpendicular to the vibration direction; there are 450 welding teeth on the base, 30 in a row in the length direction and 15 in a row in the width direction. The bottoms of adjacent welding teeth are closely connected, and the distance between the vertices is 1 mm. Since the structure and principle of the SONICS MSC 2500-20 ultrasonic welding system are well known to those skilled in the art, they will not be described in detail in this embodiment.
[0078] The tantalum foil in step (2) was overlapped on the titanium plate, that is, overlapped in a manner of tantalum on top and titanium on the bottom, with an overlap distance of 15 mm, and then the tantalum foil and the titanium plate were placed on the base of the SONICS MSC 2500-20 ultrasonic welding system.
[0079] (4) Start the SONICS MSC 2500-20 ultrasonic welding system, control the ultrasonic electrode tip to apply a vertical downward pre-pressure to the tantalum foil and the titanium plate, the pre-pressure pressure is 1.5 kN, and the pre-pressure time is 1 s; then control the ultrasonic electrode tip to simultaneously apply a vertical downward welding pressure and ultrasonic vibration in the horizontal direction to the tantalum foil and the titanium plate, wherein the ultrasonic amplitude is 60 μm, the welding pressure is 1.5 kN, the welding energy is 2000 j, the welding frequency is 20 kHz, and the welding time is 1 s; during the welding process, the welding teeth on the ultrasonic electrode tip can be embedded in the tantalum foil, and because the height of the welding teeth is greater than the thickness of the tantalum foil, and the ductility of tantalum is very good, the welding teeth on the ultrasonic electrode tip can be embedded in the tantalum foil and cause the tantalum foil to undergo plastic deformation and be embedded in the titanium plate together with the welding teeth, and the welding teeth on the base can be embedded in the titanium plate, and friction heat and plastic deformation occur between the overlapping interfaces of the tantalum foil and the titanium plate are connected together, completing the welding of the tantalum foil and the titanium plate.
[0080] Results Analysis
[0081] The samples were cut from the welded joints in the embodiment using a linear cutter. The cut samples were inlaid using an XQ-2B metallographic sample inlay machine and metal inlay powder. After inlaying, the samples were ground with sandpaper and then polished with a polishing machine. The etchant for titanium was a mixture of 3 ml H2SO4, 5 ml HNO3, 10 mL HF and 20 mL pure water, and the etchant for tantalum was a mixture of 5 ml H2SO4, 5 ml HNO3, 10 mL HF and 10 mL pure water. The etching times were 10 seconds and 120 seconds, respectively. After etching, the samples were observed for microstructure using a Zeiss Axioscope A1 optical microscope (OM) and a Tescan VAGA 3 scanning electron microscope (SEM). The macroscopic elemental composition of pure titanium and tantalum sheets was studied using a PerkinElmer Optima 8300 inductively coupled plasma emission spectroscopy (ICP-OES). The microscopic elemental composition inside the welded joint was analyzed using a Thermofisher UltraDry energy dispersive spectrometer (EDS) detector integrated in a Tescan scanning electron microscope. The crystal structure of the intermetallic compounds in the joint was calibrated using a FEITalos F200X scanning transmission electron microscope (STEM), and thin sections for TEM analysis were prepared using a FEIScios focused ion beam / scanning electron microscope (FIB-SEM). Before FIB cutting, a TEAMEDAX integrated energy dispersive spectrometer was used to confirm the target. The dimensions and three-dimensional measurements of the welded joint were performed using a Keyence VHX-6000 digital microscope system. The hardness test was performed on a Sino Eagle HV-1000 microhardness tester, and test forces of 100 gf, 50 gf, and 25 gf were applied to specific samples. The holding time was set to 10 seconds, and the detailed test information was marked in the hardness test results. The tensile-shear test used a Care IBTC-5000 in-situ tensile system, and the tensile rate was set to 0.05 mm / s.
[0082] The surface morphology of the welded joint is Figure 3 The dimensional measurement shows that the depth of the cone indentation on the upper surface is about 200 μm ( Figure 3 (a) in the figure, which is mainly caused by the deformation of the upper tantalum foil. The depth of the indentation on the bottom surface in contact with the bottom anvil is about 150 μm ( Figure 3 (d) in the figure shows that the depth value decreases with the distance from the geometric center of the electrode. The tantalum foil around the electrode indentation is slightly warped, with a buckling height of about 150 μm. The material in direct contact with the cone teeth (including the bottom titanium plate) forms neatly arranged cone indentations. The above measurements also show that the indentation depth is uniform, which preliminarily indicates that an effective connection between the tantalum and the titanium plate has been achieved.
[0083] The cross-sectional morphology of the welded joint is as follows: Figure 4As shown in the figure, the welding interface can be clearly seen, revealing the good connection between tantalum and titanium on the contact interface of the two pieces. No obvious transition layer was observed in the cross-sectional morphology, and tantalum and titanium were closely intertwined. Figure 4 The EDS mapping and BSE (Back Scattered Electron) imaging results in (d~f) highly support the above inference.
[0084] In order to better understand the metallurgical joining of tantalum and titanium in low-power ultrasonic welding, a transmission electron microscopy method was used. First, a TEM lamella was prepared using a focused ion beam (FIB-SEM). The location of the lamella is shown in Figure 2. Figure 5 The transmission electron microscopy results are shown in Figure 6 It is obvious that the target is located at the welding interface, as shown in Figure 5 As shown in the dashed box in (a) of FIG. 3 , the element composition of the welding interface was analyzed by using the energy spectrum and linear scanning, and it was found that there was a transition layer at the welding interface, and the thickness of the transition layer was about 0.3 μm, as shown in FIG. Figure 5 (e) in the figure. It is worth noting that solid-state diffusion alone is not enough to explain why this region on the bonding interface occurs in such a short time and at such a low operating temperature. It can be inferred that ultrasonic vibration may promote the diffusion of atoms at the welding interface. Studies have shown that ultrasonic vibration can significantly promote atomic diffusion by 10 to 1000 times compared to no ultrasonic vibration. In addition, SEM and TEM imaging of the thin film revealed that the grains on the titanium and tantalum sides close to the welding interface were significantly refined, with a grain size of approximately less than 1 μm, showing a typical ultrasonic vibration grain refinement effect, as shown in Figure 2. Figure 5 (d) and Figure 6 As shown in (d) in .
[0085] Selected area electron diffraction (SAED) in the titanium region revealed two typical phases, hexagonal titanium (α-Ti) and cubic titanium (β-Ti). The obtained diffraction patterns and the corresponding theoretical patterns are shown in Figure 6 (e, f) and Figure 6 As shown in (h, i) in the figure, the image results highly support this finding. It is worth noting that the titanium near the bonding interface is almost entirely cubic titanium, and the amount of β-Ti in the titanium region decreases with increasing distance from the bonding interface, indicating that the ultrasonic welding operation creates conditions that are favorable for the transformation of α-Ti to β-Ti, namely temperature. Figure 6 The bright field image shown in (d) demonstrates the above conclusion well, in which α-Ti shows dark contrast and β-Ti shows bright contrast. Figure 7 The high-resolution TEM (HRTEM) image in (e) also shows the phase boundary between α-Ti and β-Ti.
[0086] It is important to note that the body-centered cubic structure has higher plasticity than the hexagonal close-packed structure. Therefore, the distribution of cubic titanium near the bonding interface may be the key reason for achieving the connection between tantalum and titanium. Figure 7 The HRTEM image in (f) shows the metallurgical bonding of tantalum and titanium at the welding interface. It is worth noting that the crystal structures on both sides of the ultrasonic friction interface have a body-centered cubic (BCC) structure.
[0087] It can be inferred that the bonding mechanism of tantalum and titanium at low temperature is as follows: under the action of ultrasonic vibration, as the temperature of the bonding interface increases, the original hexagonal titanium (α-Ti) is partially transformed into cubic titanium (β-Ti, BCC structure). As the operating temperature gradually increases, the two metals gradually superplasticize, achieve mechanical bonding under ultrasonic kneading, and form a corresponding transition layer. Figure 7 The HRTEM image shown shows the transformation of α-Ti to β-Ti and the metallurgical bonding of tantalum and titanium is achieved at the weld interface.
[0088] The connection quality of tantalum and titanium was evaluated by tensile-shear test and hardness test. Figure 8~Figure 9 As shown. It is worth noting that since ultrasonic welding is a solid-state welding process, the temperature inside the nugget is relatively low during welding. In addition, thanks to the ultrasonic vibration, the grains inside and around the nugget are refined. Therefore, a typical heat-affected zone is not generated. These characteristics of ultrasonic welding play an important role in maintaining or even improving the mechanical properties of the welded joint.
[0089] Figure 8 (a, d) The macroscopic photos of the tensile-shear test show that the welded joint breaks at the edge of the electrode indentation on the tantalum foil, which is defined as the bearing surface. The fracture mechanism of the welded joint is as follows Figure 8 As shown in (b) in . Figure 8 The cross-sectional morphology of the welded joint in (e) shows that under the action of welding pressure, the local area of the tantalum foil is thinned, and the edge of the cone indentation becomes the weakest part of the welded joint. The tensile shear strength of the welded joint is measured to be about 295 MPa, and the elongation is about 35%. Figure 8 Combining these results with the mechanical properties of pure tantalum, as shown in (c) Figure 8As shown in (f), the ultimate tensile strength of pure tantalum is 334 MPa and the elongation is 43%. It can be seen that the ultimate tensile shear strength of the welded joint reaches 88.32% of the parent material. Interestingly, the tensile-shear test of the tantalum-titanium welded joint is essentially a stretching of the tantalum foil. This is because the bottom titanium plate is thick enough to remain unchanged during the tensile-shear test. Therefore, the tantalum foil is fixed by the welding part, specifically the bottom of the cone indentation. The rest of the tantalum foil outside the electrode indentation warps as the tensile load increases, indicating that the welding quality between ultrasonically welded tantalum and titanium is good.
[0090] Hardness test of welded joints Fig. 9 The test locations are carefully designed to cover areas with typical grain size and structural characteristics, such as the mechanical mixing area and the parent metal area. The hardness value of the parent metal is shown in Fig. 9 As shown in (d~e) in the figure, the average hardness of pure tantalum and pure titanium is 94.1 HV and 161.2 HV respectively. In contrast, the hardness of the mechanical mixing zone inside the weld joint is significantly improved, and the hardness of the local area is even twice that of pure titanium, reaching an astonishing 364.9 HV, indicating that the strengthening effect of ultrasonic vibration on the weld joint is typical. The hardness changes in the horizontal and vertical directions in the mechanical mixing zone are shown in Figure 2. Fig. 9 These results are shown in (b~c) of Figure 5~Figure 6 The combination of the grain size information shown in the FIB and TEM results can well explain the effect of ultrasonic vibration on the welded joint.
[0091] It is generally believed that materials can only be joined after they are melted. However, ultrasonic welding is a solid-state joining technique, which means that the material inside the weld nugget does not melt during the welding process. This feature represents a significant feature of this work, which investigates the effective joining of ultra-high melting point metals at relatively low temperatures.
[0092] Since the upper tantalum foil is too thin to be suitable for embedding thermocouples, the temperature inside the nugget was evaluated using a high-speed infrared thermometer. The results show that the nugget temperature reaches a peak at the moment the electrode stops vibrating, and the temperature detected on the surface of the tantalum foil is about 544°C, which is only 18.15% of the melting point of tantalum (2996°C) and 32.61% of the melting point of pure titanium (1668°C). Of course, the temperature inside the nugget zone may be higher, but since the tantalum foil is only 0.1 mm thin and tantalum has good thermal conductivity, this difference is limited. Fig.10 The temperature curve shown in (c) in Figure 1 supports this conclusion well, indicating that the temperature at the bottom of the cone indentation is about 60°C higher than that at the top, which to some extent reveals that the temperature inside the weld joint is higher than 544°C. Fig.10 As shown in (a) in .
[0093] The above results are in good agreement with previous studies evaluating the temperature field of ultrasonic welded joints. They indicate the controlled and relatively low temperature nature of the ultrasonic joining process in the nugget region and also show that metals with ultra-high melting points can achieve good welding at relatively low working temperatures.
[0094] To better explain the joining mechanism of tantalum and titanium at low temperatures, we used SEM, BSE, and EDS to carefully observe the weld joint, especially the bottom of the cone indentation. Fig.11 As shown in Figure 2, it can be seen that under the action of ultrasonic vibration, tantalum and titanium are mechanically mixed. Fig.11 (b, d) in the figure show the typical plastic flow morphology, especially the plastic flow morphology of tantalum. EDS mapping and BSE imaging results ( Fig.11 The (b, c, d) in Figure 1 highly support the above discussion, indicating that tantalum and titanium obtain superplasticity at a relatively low temperature generated by ultrasonic vibration, thereby achieving effective bonding of tantalum and titanium. A thin transition layer was observed at the tantalum-titanium welding interface, and the EDS linear scan across the welding interface ( Fig.11 The (h, j) in is highly consistent with this conclusion.
[0095] It is very interesting to combine the joining of tantalum and titanium at lower temperatures with their respective crystal structures of body-centered cubic (BCC) and hexagonal close-packed (HCP) structures. Therefore, the joining mechanism of tantalum and titanium at relatively low temperatures is well understood.
[0096] It is worth noting that the plasticity of the BCC structure is significantly better than that of the HCP structure. In addition, the ultrasonic softening effect enhances the plastic deformation of the metal. In this case, tantalum does exhibit superplasticity at high temperatures, thereby plastically flowing on the titanium surface and partially integrating into the titanium matrix. When the welding temperature is increased to above 600°C, under the action of ultrasonic vibration, the crystal structure of titanium is transformed from HCP (α-Ti) to BCC (β-Ti) structure, thereby improving the deformation capacity. At this point, both tantalum and titanium exhibit excellent plasticity. Considering the kneading and stirring effects of ultrasonic vibration, combined with the promotion of atomic diffusion by ultrasonic vibration, the gap between the attached tantalum fragments and BCC titanium at the contact interface is eliminated to form a bond, forming an interlocking ultrasonic welded joint. However, due to the short duration and low temperature of ultrasonic welding, although ultrasonic vibration promotes atomic diffusion, tantalum and titanium atoms do not have enough time to fully diffuse, and it is difficult to form a transition layer with a thickness of only about 0.5 μm. Figure 5~Figure 7 The FIB, HRTEM and HAADF images shown clearly show this transition layer.
[0097] It is also important to note that under the above welding thermal cycle, the crystal structure of tantalum remains consistent in the BCC structure. This characteristic causes the plastic deformation of tantalum foil to take precedence over titanium, indicating that the plastic flow of tantalum foil throughout the welding process will be significantly higher than that of titanium. In other words, the connection between tantalum and titanium involves the process of tantalum penetrating into titanium. This phenomenon is very obvious in the OM image and SEM image (see Figure 4 and Fig.11 ), indicating that sufficient plastic deformation is essential for forming a strong bonding interface during ultrasonic welding. So far, the intrinsic mechanism of effectively joining metals with ultra-high melting points at low temperatures has been fully understood. This will help future material scientists to achieve material joining through innovative processes, especially those involving cryogenic technology, rather than relying solely on melting materials for joining. This approach is expected to help reduce the impact of thermal cycles on the performance of welded joints.
[0098] In summary, this embodiment proposes a welding method for tantalum and titanium, a new method for connecting dissimilar materials without relying on melting and atmospheric protection, and effectively connects metal tantalum and titanium with ultra-high melting points at relatively low temperatures by ultrasonic welding with specific welding parameters. In this embodiment, pure tantalum and titanium are successfully welded in a tantalum-on-titanium-on-bottom manner with specific parameters: welding time 1 s, ultrasonic amplitude 60 μm, welding pressure 1.5 kN, and welding energy 2000 j. High-speed infrared temperature monitoring shows that the temperature of the welded joint is only about 600°C during the welding operation under this specific parameter, which is only 32.61% and 18.15% of the melting points of pure titanium and pure tantalum. Compared with other high-energy input melting welding, this method saves energy. Through microstructural observation, it was found that there were obvious plastic metal flow traces and mechanical bonding interfaces inside the welded joint, indicating that tantalum and titanium have superplasticity when welded at the welding temperature generated by the above specific parameters. Energy spectrum analysis shows that there is a transition layer with a thickness of about 0.5 μm at the interface between Ta and Ti, indicating the possibility of connecting ultra-high melting point metals at lower temperatures. Transmission electron microscopy analysis shows that under the action of ultrasonic vibration with an amplitude of 60 μm, titanium transforms from α-Ti to β-Ti at lower temperatures. HRTEM and HAADF images show the atomic diffusion and connection of tantalum and titanium, directly proving the feasibility of this new connection method.
[0099] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for welding tantalum and titanium, characterized in that: The following steps are involved: The titanium is placed on the base of the ultrasonic welding equipment; Lapping tantalum on a side of the titanium facing away from the base; Controlling the ultrasonic electrode tip of the ultrasonic welding device to move toward the base until it contacts the tantalum, and pre-pressing the tantalum and the titanium with preset pre-pressing parameters, wherein the preset pre-pressing parameters include: a pre-pressing pressure of 1.4-1.6 kN, and a pre-pressing time of 0.8-1.2 s; Controlling the tip of the ultrasonic electrode to weld the tantalum and the titanium with preset welding parameters, wherein the preset welding parameters include: ultrasonic amplitude of 56-64 μm, welding pressure of 1.4-1.6 kN, welding energy of 1900-2100 j, welding frequency of 20-22 kHz, and welding time of 0.8-1.2 s; Wherein, at least a portion of each welding tooth on the tip of the ultrasonic electrode and at least a portion of each welding tooth on the base are respectively embedded in the tantalum and the titanium, and welding grooves corresponding to the welding teeth are respectively formed on the tantalum and the titanium; The thickness of the tantalum is 0.08-0.12 mm, the thickness of the titanium is 1.5-1.7 mm, and the overlapping distance between the two is 14-16 mm.
2. The welding method according to claim 1, characterized in that: The pre-pressing pressure is 1.45-1.55 kN, and the pre-pressing time is 0.9-1.1 s; The ultrasonic amplitude is 58-62 μm, the welding pressure is 1.45-1.55 kN, the welding energy is 1950-2050 j, the welding frequency is 20-21 kHz, and the welding time is 0.9-1.1 s.
3. The welding method according to claim 1, characterized in that: The pre-pressing pressure is 1.5 kN, and the pre-pressing time is 1 s; The ultrasonic amplitude is 60 μm, the welding pressure is 1.5 kN, the welding energy is 2000 j, the welding frequency is 20 kHz, and the welding time is 1 s.
4. The welding method according to claim 1, characterized in that: The welding method further comprises: The ultrasonic electrode tip is controlled to move toward the base until at least a portion of each welding tooth on the ultrasonic electrode tip is embedded in the tantalum and the tantalum is plastically deformed to be embedded in the titanium.
5. The welding method according to claim 4, characterized in that: The welding groove is in the shape of a pyramid, the depth of the welding groove is 0.13-0.23 mm, the width of the top opening of the welding groove is 0.5-1.0 mm, and the side wall of the welding groove is at an angle of 40-50° to the ultrasonic vibration direction.
6. The welding method according to claim 5, characterized in that: The depth of the welding groove on the tantalum is 0.18~0.22mm, the depth of the welding groove on the titanium is 0.13~0.17mm, the width of the top opening of the welding groove is 0.6~0.9mm, and the side wall of the welding groove is at a 45° angle to the ultrasonic vibration direction.
7. The welding method according to claim 6, characterized in that: A plurality of rows of welding grooves corresponding to the welding teeth are formed on the tantalum and the titanium, respectively. The top openings of the welding grooves in adjacent rows are connected, and the distance between the bottoms is 0.5-1.0 mm.
8. The welding method according to any one of claims 1 to 7, characterized in that: Before the step of placing titanium on the base of the ultrasonic welding device, the welding method further comprises: Place tantalum and titanium in an ultrasonic cleaner and clean for 10-15 minutes. The cleaning agent is water and alcohol in a volume ratio of 3-5:
1. The cleaned tantalum and titanium are dried in a vacuum drying furnace at a drying temperature of 60-80° C. for a drying time of 1-2 hours.
Citation Information
Patent Citations
Ultrasonic metal welding method adopting pre-stamping deformation treatment
CN106312289A
Welding method for tantalum-titanium dissimilar metal
CN115121928A
Welding methods including formation of an intermediate joint using a solid state welding process
US20180361498A1
